Keterlibatan Ikhwanul Muslimin Dalam Konflik Suriah (2011-2019) - Gumilar Irfanullah; Anggi Yus Susilowati (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2020)
This paper traces the involvement of the Muslim Brotherhood organization and their role in the conflict in Syria that rolled from 2011 to 2019. The involvement of the Muslim Brotherhood is considered important in the context of the Syrian conflict because it has a fairly long-standing relationship with the Ba'ats government that now controls Syria. Since the 30-year exile of the organization, the Brotherhood's activity in responding to the Syrian conflict was read as a form of willingness to take part in the formation of Syria after Assad stepped down, as aspired by the Syrian opposition. This paper uses a qualitative method with a Syrian conflict case study approach (2011-2019). The dynamics of the Ikhwan's involvement in the Syrian conflict are read through the discourse of Islamism and Post-Islamism and produce some picture of the reasons behind the Ikhwan's involvement and at the same time read the extent of Ikhwan's success as an opposition in the Syrian conflict.Keywords: Muslim Brotherhood, Syrian Conflict, Islamism, Post-Islamism